Effectiveness of intervention program in improving maternal reproductive health practices among the rural poor of Bangladesh - Ghani, Ruhina Binta A; Md Abdullah Al Mamun,; Khan , Nazrul Islam (Bangladesh Journal of Nutrition, 2018)
Nutrition education, Nutritional knowledge, Sanitary and hygiene practice Reproductive and sexual ill-health accounts for 20% of the global burden of all ill-health for women and 14% for men (WHO). In Bangladesh, maternal mortality appears to be declining; however, with at least 194 maternal deaths per 100,000 births, the country still has one of the highest maternal mortality ratios in the world and the highest in South Asia. The government of Bangladesh is widely described as consistently supportive of maternal health, despite several recent changes in power. The government has enacted policies in support of maternal and newborn health along with several other policies in their development. However, many stakeholders feel that the policy commitment of the government has not translated into additional capacity or funding on the ground. Here, an attempt has been to observe where we are now and what to do for the achievement of Millennium Development Goals. A quasi experimental study was conducted by a non-government organization (BRAC) to assess the socio-demographic characteristics, environmental conditions, and obstetric information and family planning methods along with effectiveness of interventions on various issues of reproductive health. Most of the respondent was below 25 years of age (58.2%) with not participating in any income generating activities (96.5%). Majority of them (31.5%) did not complete their primary education. Family planning was adopted by 63.8% study population. A very good proportion of mother (71.4%) received ANC during their last pregnancy. A healthy child is the future of the nation which can be achieved by a healthy mother. Still delivery by skilled birth attended is poor. People still far behind to adopt family planning. Intervention programs must focus on sensitizing people on family planning. Therefore, our country will not be in the list of highest maternal mortality country. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 9-18